Comparison of waist-to-hip ratio and other obesity indices as predictors of cardiovascular disease risk in people with type 2 diabetes: a prospective cohort study from ADVANCE - Czernichow, Sébastien (2011)
AIMS: The aim of this study was to compare the strength of associations and discrimination capability of body mass index (BMI), waist circumference (WC) and waist-to-hip ratio (WHR) with cardiovascular disease risk in individuals with type-2-diabetes. METHODS AND RESULTS: 11,140 men and women were followed for a mean of 4.8 years. Cox proportional hazard models were used to compute the hazard ratios (HR) and 95% confidence intervals (95% CI) for one standard deviation (SD) increase in baseline BMI (SD: 5 kg/m(2)), WC (SD: 13 cm) and WHR (SD: 0.08) with cardiovascular disease risk. After adjustment, HR (95% CI) for WC were 1.10 (1.03-1.18) for cardiovascular events, 1.13 (1.03-1.24) for coronary events, and 1.08 (0.98-1.19) for cardiovascular deaths. Estimates for WHR were 1.12 (1.05-1.19), 1.17 (1.08-1.28) and 1.19 (1.09-1.31). BMI was not related to any of these outcomes. While the receiver operating characteristic curve could not differentiate between anthropometric variables (p-values ≥ 0.24), the relative integrated discrimination improvement statistic showed an enhancement in the discrimination capabilities of models using WHR for cardiovascular outcomes, except for cerebrovascular events. CONCLUSION: Strengths of associations and discrimination statistics suggested that WHR was the best predictor of cardiovascular events and mortality in patients with type-2-diabetes and BMI the worst.